2016
DOI: 10.21037/sci.2016.09.04
|View full text |Cite
|
Sign up to set email alerts
|

TET2 mutations were predictive of inferior prognosis in the presence of ASXL1 mutations in patients with chronic myelomonocytic leukemia

Abstract: Background: Somatic mutations involving epigenetic regulators, histone modification and chromatin regulation, splicing components, transcription factors and signaling regulator genes are common in chronic myelomonocytic leukemia (CMML) patients. It has been consensus that ASXL1 mutations have adversely impact on overall survival (OS), while the effect of TET2 mutations remains controversial and undefined.Methods: ASXL1 and TET2 mutations were analyzed in 141 patients with CMML using Sanger sequencing, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…And the mutant mice developed phenotypes recapitulating human low-risk MDS and some of the mice developed MDS/myeloproliferative neoplasmlike disease after long latency (Uni et al, 2019). Consistent with the clinical prognosis (Cui et al, 2015(Cui et al, , 2016, hematopoieticspecific deletion of both Asxl1 and Tet2 leads to a much earlier onset of MDS than the deletion of Asxl1 or Tet2 alone. In support, Asxl1 deficiency accompanied with haploinsufficiency of Nf1 or KRas oncogenic mutation accelerates the development of myeloid leukemia in mice (Abdel-Wahab et al, 2012;Zhang et al, 2018).…”
Section: Asxl1 Mutations In Myeloid Malignancies: Loss or Gain-of-funmentioning
confidence: 70%
See 1 more Smart Citation
“…And the mutant mice developed phenotypes recapitulating human low-risk MDS and some of the mice developed MDS/myeloproliferative neoplasmlike disease after long latency (Uni et al, 2019). Consistent with the clinical prognosis (Cui et al, 2015(Cui et al, , 2016, hematopoieticspecific deletion of both Asxl1 and Tet2 leads to a much earlier onset of MDS than the deletion of Asxl1 or Tet2 alone. In support, Asxl1 deficiency accompanied with haploinsufficiency of Nf1 or KRas oncogenic mutation accelerates the development of myeloid leukemia in mice (Abdel-Wahab et al, 2012;Zhang et al, 2018).…”
Section: Asxl1 Mutations In Myeloid Malignancies: Loss or Gain-of-funmentioning
confidence: 70%
“…And the presence of the mutations is associated with adverse outcomes ( Gelsi-Boyer et al, 2009 , 2010 ; Boultwood et al, 2010 ; Chou et al, 2010 ; Metzeler et al, 2011 ; Thol et al, 2011 ; Itzykson et al, 2013 ). In CMML patients, additional TET2 mutations were associated with shorter survival in the presence of ASXL1 mutations ( Cui et al, 2015 , 2016 ). In contrast, ASXL1 mutations are mutually exclusive with DNMT3A , NPM1 , and SF3B1 mutations ( Asada et al, 2019 ).…”
Section: Asxl1 Mutations In Myeloid Malignancies: Loss or Gamentioning
confidence: 99%
“…According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years 4,35,50 . We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan 16,22,27 and China, 6,43,49,56–63 ), and the results showed that the median age of CMML patients in Eastern countries was younger (38–70 years vs. 44–73 years), and the median age of CMML patients undergoing allo‐HSCT was similar in Eastern and Western countries (38–63 years vs. 44–64 years). However, the age of CMML patients undergoing allo‐HSCT was lower in both Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…TET2 gene in this region is a tumor-suppressor gene 19 . The deletion or mutation of TET2 often predict inferior prognosis in patients with chronic myelomonocytic leukemia 20 . Although aberration in chromosome 5 has been considered as the most prevalent chromosomal lesion in MDS, some cryptic defects which affect additional key genes have not been clarified comprehensively.…”
Section: Discussionmentioning
confidence: 99%